Penampilan Agronomi dan Uji Toleransi Naungan Galur Dihaploid Padi Gogo Hasil Kultur Antera - Mara, Kartika Kirana Sangga; Purwoko, Bambang Sapta; ,, Eko Sulistyono; Dewi, Iswari Saraswati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTShifting of upland rice cultivation to marginal land faces drought stress, while planting under young plantation faces shading stress. There should be lines or varieties with good agronomic character and tolerant to the shading stress. Lines used in this experiment were obtained from anther culture, i.e., III3-4-6-1, I5-10-1-1, WI-44, GI-7, O18-b-1, IW-67, IG-19, IG-38, IW-56, B13-2-e. Two experiments were conducted, i.e., agronomic performance experiment and shading tolerance experiment with a quick test method at seedling phase. Batutegi and Way Rarem were used as check varieties in the agronomic experiment. In shading tolerance experiment, Kalimutu was used as sensitive check and Jatiluhur was tolerant check varieties. The results of experiment indicated that B13-2-e (4.64 ton ha-1) and WI-44 line (4.05 ton ha-1) dihaploid lines showed high grain yield and comparable to Way Rarem (4.95 ton ha-1). B13-2-e and WI-44 lines were tolerant to shading. Another tolerant lines to shading, i.e., I5-10-1-1, O18-b-1, and IW-56. B13-2-e and WI-44 lines were recommended to advanced verification on multiple cropping system.Keywords: dry land, multiple cropping